Decreasing Youth Hyperactivity and Inattention Problems Through Mentoring: Evaluation of the Mentor-UP Program - Marino, Claudia; Cardillo, Ramona; Canale, Natale; Lenzi, Michela; Bergamin, Marisa; Bonichini, Sabrina; Santinello, Massimo (Frontiers in Education, 2021)
Few studies so far have analysed the potential role of mentoring in decreasing hyperactivity and inattention problems. The aim of the current study is to investigate the impact of the Italian Mentor-UP mentoring program on hyperactivity and inattention problems in a non-clinical sample of mentees. “Mentor-UP” is a weekly school- and community-based mentoring program implemented in northern Italy over a period of eight months. The sample included 468 students, 65 from the experimental group (mentees) and 403 as comparison group. Participants’ age ranged between 8 and 14 years (M=11.31, SD=1.40), 46% were females and 20% were non-Italian youths. Students reported their levels of hyperactivity and inattention problems at the beginning and at the end of the program. A significant interaction between time and group revealed a significant effect of the program on hyperactivity and inattention problems (B=-0.10, t(450)=-2.00, p=.04), which decreased in mentees (Cohen’s d = -.21) but not in the comparison group. Results supported the effectiveness of Mentor-UP in decreasing youths’ hyperactivity and inattention. This might be due to the structural characteristics of the mentoring relationships established in the context of Mentor-UP.